Histologically validated scoring system for the assessment of hock burn in broilers. Issue 3 (3rd May 2020) - Louton, H.; Piller, A.; Bergmann, S.; Erhard, M.; Stracke, J.; Spindler, B.; Kemper, N.; Schmidt, P.; Schade, B.; Boehm, B.; Kappe, E.; Bachmeier, J.; et al.
ABSTRACT: The assessment of bird-based welfare indicators plays an important role in the evaluation of bird welfare. The aim of the study was to histologically validate a visual scoring system for hock burn in broilers and to detect threshold values of a visual score to define welfare-relevant alterations in terms of mild lesions or ulcers of the hock. We collected 200 hocks of 39- to 42-day-old Ross 308 broilers after the slaughter process. Each hock was scored visually ("macro scores" 0–4) and evaluated histologically ("micro scores" 0–3), with high scores representing more severe lesions. Although we found a tendency for higher micro scores with increasing macro scores, an exact allocation of macro to micro scores was not possible. For example, macro score 1 could represent micro scores 1, 2 and 3, whereas macro scores 3 and 4 always represented micro score 3 (ulcer). The conditional probability of certain micro scores for given macro scores was estimated using a multinomial logistic regression model. Ulcer showed the highest probability at macro score 1, whereas mild lesions were not found to have an estimated highest probability at any macro score. The depth of inflammation of hock burn lesions increased with increasing macro scores up to macro score 3 with an average depth of 1019 µm. Visually more severe and deeper lesions were also histologically rated with higher scores. Thus, considering limitations, the herein validated macroscopic assessment scheme for hock burn allows an estimation of histological alterations in hocks of broilers. RESEARCH HIGHLIGHTS Histological validation of a visual assessment scheme for hock burn in broilers. Tendency for higher micro scores with increasing macro scores. Estimation of histological score via macro score possible with limitations. Histological depth of inflammation increased with an increasing macro score.